Effect of Supplementation of Bypass Fat and Mineral Mixture on Uterine Involution and Fertility in Gir Cows - Sahoo, Bhubaneswar; Panchal, Mahesh T; Patel, Dignesh K; Patel, Jagadish A (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The study was carried out on 18 advanced pregnant Gir cows, under two treatment (Group I, II) and control (Group III) groups, 6  cows in each. The cows under Group III were maintained as per routine farm feeding schedule, while cows under Group I and II were  supplemented with mineral mixture containing rumen protected methionine and lysine @ 50 g/day/head. Additionally, animals in  group I were supplemented with bypass fat @ at least 100 g/d/h during 30 days prepartum till 60 days postpartum. The postpartum  reproductive events were monitored by USG (5-10 MHz linear array transducer). The mean cervical diameter and wall thickness in cows  under control Group III were the highest on all days postpartum as compared to nutrient supplemented groups I & II. The values on day  7 were highest in all three groups and decreased gradually (p
Keywords: Bypass fat; Cattle; Conception rate; Involution; Mineral supplement; Peripartum